A Case Study of Intractable Vomiting with Final Diagnosis of Neuromyelitis Optica. (5th October 2015) - Bramson, Rachel; Hairrell, Angela
Abstract : This case study presents a patient living in a suburban/rural community who received appropriate referral to secondary and tertiary care for nausea and vomiting, accompanied by waxing and waning neurological symptoms, yet proved difficult to diagnose. This patient is presented to draw attention to a rare neurological disorder which should be included in the differential diagnosis of nausea and vomiting with some key neurological complaints, even in the absence of physical findings.